A revision of the soft coral genus, Eunephthya Verrill, 1869 (Anthozoa: Octocorallia: Nephtheidae), with a description of four new species from South Africa - Mcfadden, Catherine S.; van Ofwegen, Leen P. (Zootaxa, 2012)
Based on the results of morphological and molecular phylogenetic analyses of newly collected material, we reinstate thesoft coral genus Eunephthya Verrill, 1869 for a group of species endemic to South Africa. Eunephthya is morphologicallyand phylogenetically distinct from the zooxanthellate, tropical genus Capnella Gray, 1869 with which it had been synon-ymized. In Eunephthya the polyp sclerites include unilaterally spinose or leaf spindles, and the sclerites of the stalk surfaceand interior (when present) are small radiates and spheroids. In contrast, C. imbricata, the type species of Capnella, hasleaf clubs and leaf-capstans in the polyps and stalk surface, and large ovals and irregular forms in the interior. We describefour new species of Eunephthya from Algoa Bay, South Africa—E. celata, E. ericius, E. granulata, and E. shirleyae— and propose a new combination, E. susanae.Keywords. Molecular phylogenetics, Capnella, mtMutS, COI, 28S rDNA, endemism